(untitled) (Journal of Mathematical Study, 2015)
The purpose of this paper is to prove some weak convergence theorems for mixed type asymptotically nonexpansive mappings with mean errors in uniformly convex Banach spaces. The results presented in this paper extend the corresponding results in the references.